Body Dysmorphic Disorder Association with Psychosis: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Body Dysmorphic Disorder; Fluoxetine; Monosymptomatic Hypochondriacal Psychosis; Risperidone